The Rise of Wine among Ancient Civilizations across the Mediterranean Basin - Mkrtich Harutyunyan; Manuel Malfeito-Ferreira (Heritage, 2022)
The purpose of this work is to present the archaeological and historical background of viticulture and winemaking from ancient times to the present day in the Mediterranean basin. According to recent archaeological, archaeochemical and archaeobotanical data, winemaking emerged during the Neolithic period (c. 7th–6th millennium BC) in the South Caucasus, situated between the basins of the Black and Caspian Seas, and subsequently reached the Iberian Peninsula and Western Europe during the local beginning of Iron Age (c. 8th century BC), following the main maritime civilizations. This review summarises the most relevant findings evidencing that the expansion of wine production, besides depending on adequate pedo-climatic conditions and wine-growing practices, also required the availability of pottery vessels to properly ferment, store and transport wine without deterioration. The domestication of wild grapevines enabled the selection of more productive varieties, further sustaining the development of wine trade. Other fermented beverages such as mead and beer gradually lost their relevance and soon wine became the most valorised. Together with grapes, it became an object and a system of value for religious rituals and social celebrations throughout successive ancient Western civilizations. Moreover, wine was used for medicinal purposes and linked to a wide variety of health benefits. In everyday life, wine was a pleasant drink consumed by the elite classes and commoner populations during jubilee years, festivals, and banquets, fulfilling the social function of easy communication. In the present work, emphasis is put on the technical interpretation of the selected archaeological and historical sources that may explain present viticultural and oenological practices. Hopefully, this review will contribute to nurturing mutual understanding between archaeologists and wine professionals.